Youth life satisfaction during the COVID-19 pandemic in a cross-national comparison - Golo Henseke; Ingrid Schoon; Christoph Schimmele; Rubab Arim; Hans Dietrich; Aisling Murray; Emer Smyth; Véronique Dupéré (Economic and Social Reports)
Little is known about cross-national differences in the decline of youth life satisfaction during the COVID-19 pandemic. This study compares youth in Canada, Germany, Ireland, and the United Kingdom on life satisfaction before and during the pandemic.